Multilocus Sequence Typing of Genital Chlamydia trachomatis in Norway Reveals Multiple New Sequence Types and a Large Genetic Diversity - Gravningen, Kirsten Midttun; Christerson, Linus; Furberg, Anne-Sofie; Simonsen, Gunnar Skov; Ödman, Kristina; Ståhlsten, Anna; Herrmann, Björn (PLoS ONE, 2012)
Gravningen's doctoral thesis, available in Munin at http://hdl.handle.net/10037/5649 The Chlamydia trachomatis incidence rate in Finnmark, the most northern and sparsely populated county in Norway, has been twice the national average. This population based cross-sectional study among Finnmark high school students had the following aims: i) to examine distribution of multilocus sequence types (STs) of C. trachomatis in a previously unmapped area, ii) to compare chlamydia genetic diversity in Finnmark with that of two urban regions, and iii) to compare discriminatory capacity of multilocus sequence typing (MLST) with conventional ompA sequencing in a large number of chlamydia specimens. ompA sequencing and a high-resolution MLST system based on PCR amplification and DNA sequencing of five highly variable genetic regions were used. Eighty chlamydia specimens from adolescents aged 15–20 years in Finnmark were collected in five high schools (n = 60) and from routine clinical samples in the laboratory (n = 20). These were compared to routine clinical samples from adolescents in Tromsø (n = 80) and Trondheim (n = 88), capitals of North and Central Norway, respectively. ompA sequencing detected 11 genotypes in 248 specimens from all three areas. MLST displayed 50 STs providing a five-fold higher resolution. Two-thirds of all STs were novel. The common ompA E/Bour genotype comprised 46% and resolved into 24 different STs. MLST identified the Swedish new variant of C. trachomatis not discriminated by ompA sequencing. Simpson's discriminatory index (D) was 0.93 for MLST, while a corrected Dc was 0.97. There were no statistically significant differences in ST genetic diversity between geographic areas. Finnmark had an atypical genovar distribution with G being predominant. This was mainly due to expansion of specific STs of which the novel ST161 was unique for Finnmark. MLST revealed multiple new STs and a larger genetic diversity in comparison to ompA sequencing and proved to be a useful tool in molecular epidemiology of ...